54.3k views
1 vote
F (x) = 3x – 1 and f –1is the inverse of f, what is the value of f –1 (3)?

1 Answer

2 votes

The value of the inverse at f-1(3) is
(4)/(3).


To find this, we first need to find the inverse function. We can do so by switching the f(x) and x value. Then we need to solve for the new f(x). The result will be the inverse function. The work for this function is below.


f(x) = 3x - 1 ----> Switch the x and f(x)

x = 3f(x) - 1 ----> Add 1 to both sides

x + 1 = 3f(x) ----> Divide both sides by 3.

f(x) =
(x + 1)/(3)


Now that we have the inverse function, we can evaluate it at x = 3


f(x) =
(x + 1)/(3)

f(3) =
(3 + 1)/(3)

f(3) =
(4)/(3)

User Kenneth Spencer
by
5.9k points